Carbon Nitride Photocatalysts with Integrated Oxidation and Reduction Atomic Active Centers for Improved CO2 Conversion. Issue 34 (8th July 2022) - Ou, Honghui; Ning, Shangbo; Zhu, Peng; Chen, Shenghua; Han, Ali; Kang, Qing; Hu, Zhuofeng; Ye, Jinhua; Wang, Dingsheng; Li, Yadong
Abstract: Single‐atom active‐site catalysts have attracted significant attention in the field of photocatalytic CO2 conversion. However, designing active sites for CO2 reduction and H2 O oxidation simultaneously on a photocatalyst and combining the corresponding half‐reaction in a photocatalytic system is still difficult. Here, we synthesized a bimetallic single‐atom active‐site photocatalyst with two compatible active centers of Mn and Co on carbon nitride (Mn1 Co1 /CN). Our experimental results and density functional theory calculations showed that the active center of Mn promotes H2 O oxidation by accumulating photogenerated holes. In addition, the active center of Co promotes CO2 activation by increasing the bond length and bond angle of CO2 molecules. Benefiting from the synergistic effect of the atomic active centers, the synthesized Mn1 Co1 /CN exhibited a CO production rate of 47 μmol g −1 h −1, which is significantly higher than that of the corresponding single‐metal active‐site photocatalyst. Abstract : Mn and Co bimetallic hetero‐single‐atoms were introduced in carbon nitride photocatalysts as redox‐active sites for CO2 conversion. The construction of a bimetallic single atom as a redox site greatly promotes the separation and transfer of charges, thereby exhibiting an excellent CO2 conversion performance.